Tectonic Evolution of the Pamir Recorded in the Western Tarim Basin (China): Sedimentologic and Magnetostratigraphic Analyses of the Aertashi Section. Issue 2 (8th February 2019) - Blayney, Tamsin; Dupont‐Nivet, Guillaume; Najman, Yani; Proust, Jean‐Noël; Meijer, Niels; Roperch, Pierrick; Sobel, Edward R.; Millar, Ian; Guo, Zhaojie
Abstract: The northward indentation of the Pamir salient into the Tarim basin at the western syntaxis of the India‐Asia collision zone is the focus of controversial models linking lithospheric to surface and atmospheric processes. Here we report on tectonic events recorded in the most complete and best‐dated sedimentary sequences from the western Tarim basin flanking the eastern Pamir (the Aertashi section), based on sedimentologic, provenance, and magnetostratigraphic analyses. Increased tectonic subsidence and a shift from marine to continental fluvio‐deltaic deposition at 41 Ma indicate that far‐field deformation from the south started to affect the Tarim region. A sediment accumulation hiatus from 24.3 to 21.6 Ma followed by deposition of proximal conglomerates is linked to fault propagation into the Tarim basin. From 21.6 to 15.0 Ma, increasing accumulation rates of fining upward clastics is interpreted as the expression of a major dextral transtensional system linking the Kunlun to the Tian Shan ahead of the northward Pamir indentation. At 15.0 Ma, the appearance of North Pamir‐sourced conglomerates followed at 11 Ma by Central Pamir‐sourced volcanics coincides with a shift to E‐W compression, clockwise vertical‐axis rotations and the onset of growth strata associated with the activation of the local east vergent Qimugen thrust wedge. Together, this enables us to interpret that Pamir indentation into Tarim had started by 24.3 Ma, reached the study location by 15.0 Ma and had passed it by 11 Ma, providing kinematic constraints on proposed tectonic models involving intracontinental subduction and delamination. Key Points: ~41 Ma, retreat of the Tarim Sea coincides with tectonic subsidence attributed to the effects of uplift of the Tibetan plateau to the south From 24.3–21.6 Ma a depositional hiatus followed by fining upward conglomeratic deposition is attributed to fault propagation into the Tarim At 15.0 Ma, Pamir sourced material, a shift to EW compression and clockwise vertical‐axis rotation indicates the Pamir had reached Aertashi